Proceedings of the 9th Workshop on Computational Approaches to Subjectivity, Sentiment and Social Media Analysis 2018
DOI: 10.18653/v1/w18-6245
|View full text |Cite
|
Sign up to set email alerts
|

Super Characters: A Conversion from Sentiment Classification to Image Classification

Abstract: We propose a method named Super Characters for sentiment classification. This method converts the sentiment classification problem into image classification problem by projecting texts into images and then applying CNN models for classification. Text features are extracted automatically from the generated Super Characters images, hence there is no need of any explicit step of embedding the words or characters into numerical vector representations. Experimental results on large social media corpus show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…For fine-tuning all models on a target task, we follow the same parameters that were used in the original implementation. 121314 (2017) and Sun et al (2018) 6 Results…”
Section: Fine-tuningmentioning
confidence: 99%
See 2 more Smart Citations
“…For fine-tuning all models on a target task, we follow the same parameters that were used in the original implementation. 121314 (2017) and Sun et al (2018) 6 Results…”
Section: Fine-tuningmentioning
confidence: 99%
“…To the best of our knowledge, the current state-of-theart for Japanese text classification uses shallow (context-free) word embeddings for text classification (Peinan and Mamoru, 2015;Nio and Murakami, 2018). Sun et al (2018) proposed the Super Characters method that converts sentence classification into image classification by projecting text into images. Zhang and LeCun (2017) did an extensive study of different ways of encoding Chinese/Japanese/Korean (CJK) and English languages, covering 14 datasets and 473 combinations of different encodings including one-hot, character glyphs, and embeddings and linear, fasttext and CNN models.…”
Section: Text Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with CNN and SVM, the Bi-LSTM model shows good performance in this experiment. However, compared with the current SOTA (State of the Arts) model in the field of sentiment analysis, there are still some deficiencies [55] 85 It can be seen from the above table that the Bi-LSTM model mentioned in this paper has a certain gap in Accuracy, Recall, F1-Score and other indicators compared with SOTA. The reason for the difference in accuracy should be attributed to the insufficient number of samples in the training set, and the quality is also a factor limiting the accuracy.…”
Section: Comparative Experiments With Sotamentioning
confidence: 93%
“…However, this reliance upon one-dimensional embeddings may soon come to change. Recent NLP research has shown that the two-dimensional embedding of the Super Characters method [33] is capable of achieving stateof-the-art results on large dataset benchmarks. The Super Characters method is a two-step method that was initially designed for text classification problems.…”
Section: Introductionmentioning
confidence: 99%